Proceso crediticio y su impacto en el presupuesto del Banco Guayaquil sucursal Santo Domingo periodo 2013-2014, manual de administración de riesgos crediticio. - Sánchez Cepeda, Nadya Gissela (2015)
He banking sector is a company that generates resources, which invests in helping their clients obtain consumer credit and other according the policy established by the financial institution, in the same way is subject to credit risk. The Banco Guayaquil is Ecuador's largest financial services network. An Ecuadorian bank with AAA rating, the highest rating of Banca Ecuadorian institutional effort reflected in its solidity, liquidity and profitability. Through balances presented by Banco Guayaquil Branch Santo Domingo is evident that this institution is very strong as long as his administration remains efficient, the study was conducted with a representative sample of clients and Bank staff to establish their commitment to the bank for a possible situation of Credit Risk. Taking into account the credit risk index is below the limits set by the supervisory authority and control, it is suggested to the institution not neglect the processes established to minimize credit risk through risk management as an effective procedure to prevent delinquency, through tracking and monitoring their credit operations. The credit risk management must be specialized according to the segment to which each client belongs to strengthen the tools to efficiently monitor the performance of the portfolio generated and compliance with the limits